1968
DOI: 10.1002/hlca.19680510827
|View full text |Cite
|
Sign up to set email alerts
|

Über die Entstehung von α‐Keto‐carbonium‐Ionen bei der säurekatalysierten Hydrolyse von Diazoketonen. (Vorläufige Mitteilung)

Abstract: Summary. Secondary deactivated aliphatic diazo compounds (diazo-ketones R-CO-CN,-R'; diazo-esters ROOC-CN,-R'; 1,1, I-trifluoro-2-diazopropane) are hydrolyscd by the A -S E~ mechanism comprising rate determining protonation of the substrate, followed by decomposition. Product analysis shows that the dccomposition of the secondary diazonium ions is monomolccular, without intervention of a nucleophile.The corresponding primary diazo compounds (R-CO-CHN,, ROOC-CHN, and CF,-CHN,) are hydrolysed by the A-2 mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1969
1969
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…The reaction proceeded at room temperature and worked for aromatic (66), heteroaromatic (67), and aliphatic (68) substrates. Mechanistically, difluorocyclopropene 69 and CF 3 CHN 2 (1) first underwent [3 + 2]-cycloaddition into intermediate 70 (Scheme 14).…”
Section: Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction proceeded at room temperature and worked for aromatic (66), heteroaromatic (67), and aliphatic (68) substrates. Mechanistically, difluorocyclopropene 69 and CF 3 CHN 2 (1) first underwent [3 + 2]-cycloaddition into intermediate 70 (Scheme 14).…”
Section: Preparationmentioning
confidence: 99%
“…The hydrolysis was performed at room temperature (Scheme 38). 66 In 1979, Fields and Tomlinson observed that CF 3 CHN 2 (1) reacted with trifluoroacetonitrile to form N-alkylated product 127 in 84% yield (Scheme 26). 2 The first systemic study on the reaction of CF 3 CHN 2 (1) with nucleophiles was performed by Dorn and Koller in 1982 (Scheme 39).…”
Section: Reaction With H + (Protonation)mentioning
confidence: 99%
See 1 more Smart Citation
“…En effet, dCjk les homologues secondaires des diazoiques susmentionnCs prCsentent la protonation du carbone normale dCterminant la vitesse de la &action (mbcanisme A S & ) [4]. I1 serait donc trks intkressant de comparer les &apes de protonation du carbone en prCCquilibre ctrapide,, avec les protonations ctlentesa du type A -S E~.…”
Section: Echanges Isotopiques D'hydroghne T-h T-d D-h Et H-d De La unclassified
“…By analogy with reversible protonation, this can be expected for primary diazo compounds (-CHN,) deactivated by electron withdrawing groups like ROOC-, R-CO-[12j, I?&- [13] or ArS0,. In diazoalkanes, however, protonation is slower than loss of N,; in agreement with this, we never observed the formation of nitrile oxides, nor of products formed from them, starting with diazoethane, diazopropane, diazoisobutane, or plienyldiazometliane 6 ) .…”
mentioning
confidence: 99%